2006
DOI: 10.1038/sj.bjp.0706726
|View full text |Cite
|
Sign up to set email alerts
|

GW627368X ((N‐{2‐[4‐(4,9‐diethoxy‐1‐oxo‐1,3‐dihydro‐2H‐benzo[f]isoindol‐2‐yl)phenyl]acetyl} benzene sulphonamide): a novel, potent and selective prostanoid EP4 receptor antagonist

Abstract: sulphonamide (GW627368X) is a novel, potent and selective competitive antagonist of prostanoid EP 4 receptors with additional human TP receptor affinity. 2 At recombinant human prostanoid EP 4 receptors expressed in HEK293 cells, GW627368X produced parallel rightward shifts of PGE 2 concentration-effect (E/[A]) curves resulting in an affinity (pK b ) estimate of 7.970.4 and a Schild slpoe not significantly different from unity. The affinity was independent of the agonist used. 3 In rings of phenylephrine preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 32 publications
3
56
1
Order By: Relevance
“…A simple explanation for this discrepancy is the sensitivity of functional EP receptors of the various systems to EP receptor-related compounds. Likewise, the sensitivity to PGE 2 of the receptors in both pig vasculature and cell systems in the study by Wilson et al [22] is also two orders of magnitude higher than the sensitivity for PGE 2 at the receptors in this study; around 2-3 nM versus 200 nM.…”
Section: Ep 4 Antagonistmentioning
confidence: 68%
See 1 more Smart Citation
“…A simple explanation for this discrepancy is the sensitivity of functional EP receptors of the various systems to EP receptor-related compounds. Likewise, the sensitivity to PGE 2 of the receptors in both pig vasculature and cell systems in the study by Wilson et al [22] is also two orders of magnitude higher than the sensitivity for PGE 2 at the receptors in this study; around 2-3 nM versus 200 nM.…”
Section: Ep 4 Antagonistmentioning
confidence: 68%
“…Thus, time intervals were adjusted to the time to reach the full effect of a particular drug. To better characterize the EP 4 receptor's possible involvement in secretion, the selective EP 4 antagonist GW627368X [22] was added in a dose of 2 μ M 25 min. prior to application of PGE 2 , butaprost or OH-PGE 1 .…”
Section: Mountingmentioning
confidence: 99%
“…We found that incubation of cardiomyocytes with the specific inhibitors of EP4, GW627368X and AH23848B [23,24], abolishes the PGE 2 -induced phosphorylation of nuclear Stat3 ( Fig. 2A).…”
Section: Pge 2 Induces Nuclear Stat3 Phosphorylation Via Ep4mentioning
confidence: 87%
“…Consent was obtained from each donor, and donors were de-identified. Human washed platelets were prepared as described previously (Wilson et al, 2006). Experiments were performed in the presence of the selective TP receptor antagonist SQ-29548 (1 M) and indomethacin (1 M).…”
Section: Isolated Tissue Preparationmentioning
confidence: 99%